Penerapan Alat Bukti Elektronik dalam Perkara Perceraian Perspektif Undang-Undang Nomor 1 Tahun 2024: Studi Putusan Nomor 1257/Pdt.G/2024/PA.Mlg - Muhammad Farhan Abbas; Burhanudin Burhanudin; Harry Yuniarti (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2026)
The advancement of digital technology has transformed evidentiary practice in Indonesian courts, including divorce cases before Religious Courts. Electronic evidence such as chat screenshots and social media posts is now commonly submitted by litigants to support their claims. This article examines the application of electronic evidence in Decision Number 1257/Pdt.G/2024/PA.Mlg of the Malang Religious Court in light of Law Number 1 of 2024 on the Second Amendment to the Electronic Information and Transactions Law (ITE Law). Using a normative juridical method with statute and case approaches, this study finds that the panel of judges admitted five items of electronic evidence submitted by the respondent-husband, namely printed online news, social media screenshots, and WhatsApp conversation captures, and accorded them full evidentiary weight since their content was not contested by the opposing party. Rather than proving the grounds for divorce, this evidence became a decisive consideration in awarding child custody (hadhanah) to the father. The study further finds that the panel still grounded its reasoning in Article 5 of Law Number 11 of 2008 as amended by Law Number 19 of 2016, without explicit reference to Law Number 1 of 2024, even though the latter was already in force when the decision was rendered indicating a gap in updating statutory citation practice in religious court adjudication.